A numerical assessment on heat transfer and flow characteristics of nanofluid in tubes enhanced with a variety of dimple configurations. (1st October 2020) - Firoozi, AtaOllah; Majidi, Sahand; Ameri, Mohammad
Highlights: Innovative geometrical parameters are presented for dimple shaped roughness. Shear-thinning behavior of Alumina/Water nanofluid is studied in the dimpled tubes. Passive techniques are combined in order to investigate synergy in heat transfer. A remarkable value of 3.12 is achieved for PEC in the present study. Abstract: Heat transfer performance and flow characteristics in tubes enhanced with dimples have been studied numerically. Innovative geometrical parameters including dimple filling angle, dimple height, and dimple pitch are presented for dimple shaped roughness applied on tube surfaces. Water and Al2 O3 /Water nanofluid are considered as working fluids in steady three-dimensional simulations, where Reynolds number ranged from 500 to 4000. Nanoparticle volume fractions are taken to be 1%, 2%, and 4% in this study. Both Newtonian and shear-thinning models are used to describe rheological behavior of the nanofluid. Results show that overall performance of the enhanced tubes increases with decreasing dimple pitch, increasing dimple height, and increasing filling angle in the case of water flowing through the tubes. Moreover, maximum improvement in performance occurs at Re = 2000 while using 4% non-Newtonian (shear-thinning) nanofluid in tube with specifications of 120° dimple filling angle, 2.0 mm dimple height, and dimple pitch equal to one dimple diameter. Highest obtained PEC value is 3.12, which ranks amongst uppermost values regarding internal flows in circular conduits with modified surfaces reported in the literature.